Revision of Pyrrhalta (Coleoptera: Chrysomelidae: Galerucinae) species with maculate elytra - Bezděk, Jan; Lee, Chi-Feng (Zootaxa, 2019)
Pyrrhalta Joannis, 1865 species with maculate elytra are revised. Pyrrhalta maculata is shown to be a complex of several species. Seven species are recognized: P. maculata Gressitt & Kimoto, 1963 (Fujian, Taiwan), P. carolusi sp. nov. (Laos, Thailand), P. kaboureki sp. nov. (Sumatra), P. kambaitiensis sp. nov. (Myanmar), P. lucka sp. nov. (Laos, Thailand, Yunnan), P. schillhammeri sp. nov. (Laos) and P. tsoui sp. nov. (Taiwan). Colour photos of habitus, as well as drawings of male and female genitalia are provided.